2019
DOI: 10.3892/mmr.2019.10553
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside�Rb1 prevents steroid‑induced avascular necrosis of the femoral head through the bone morphogenetic�protein‑2 and vascular endothelial growth factor pathway

Abstract: At present, the molecular mechanism underlying the protective effect of Ginsenoside Rb1 remains unclear. The present study was designed to investigate whether Ginsenoside Rb1 weakened the steroid-induced avascular necrosis of the femoral head (SANFH) and to explore the possible mechanisms of the above effects. As a result, it was revealed that Ginsenoside Rb1 was protective against steroid-induced avascular necrosis and inhibited serum osteocalcin in a rat model of SANFH. Ginsenoside Rb1 reduced inflammation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Steroid-induced avascular necrosis of the femoral head (SANFH) is a class of non-traumatic femoral head injury that can trigger osteoclast and bone marrow necrosis due to local blood circulation disorders (Wu et al, 2019). The precise mechanism of SANFH remains unclear and may be associated with various factors such as apoptosis and inflammation (Ye et al, 2019). In vitro experiment has shown that SPS can inhibit caspase-3 activation in the osteoblasts of rats and promote bone formation (Cui et al, 2018).…”
Section: Protective Effect Against Steroid-induced Avascular Necrosis Of the Femoral Headmentioning
confidence: 99%
“…Steroid-induced avascular necrosis of the femoral head (SANFH) is a class of non-traumatic femoral head injury that can trigger osteoclast and bone marrow necrosis due to local blood circulation disorders (Wu et al, 2019). The precise mechanism of SANFH remains unclear and may be associated with various factors such as apoptosis and inflammation (Ye et al, 2019). In vitro experiment has shown that SPS can inhibit caspase-3 activation in the osteoblasts of rats and promote bone formation (Cui et al, 2018).…”
Section: Protective Effect Against Steroid-induced Avascular Necrosis Of the Femoral Headmentioning
confidence: 99%
“…SANFH rat model (n 44) was induced by 50 mg/kg DEX injected into the gluteus muscle twice a week for 6 weeks, and 36 rats with successful modeling were selected for the following experiments (Ye et al, 2019). The successful modeling rats were assigned into the SANFH group (modeling rats, n 6), and the remaining rats were administrated with Ato (15 mg/kg/day), (Baranowski et al, 2019) for two weeks after DEX injection.…”
Section: Establishment Of Sanfh Rat Modelmentioning
confidence: 99%
“…RIPA buffer (Beyotime Biotechnology Co., Ltd., Shanghai, China) was used to split the sample for 1 h and samples were centrifuged at 4°C at 12,000 xg for 10 min to collect the supernatant. The inflammatory factors tumor necrosis factor (TNF)-α (H052) and interleukin (IL)-1β (H002), and the oxidative stress indices (malondialdehyde, MDA, A003-1-2; superoxide dismutase, SOD, A001-3-2), catalase (CAT, A007-1-1), ALP (A059-2-2) and OST (H152), and caspase-3 activity were detected using corresponding kits (Beyotime) (Xiao et al, 2018;Ye et al, 2019).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Excessive oxidative stress leads to an imbalance between bone resorption and bone formation, thereby leading to loss of bone mineral density [13]. Multiple drugs exerted therapeutic effects on ONFH through their antioxidative properties [14][15][16], highlighting the significance of oxidative stress in the pathogenesis of ONFH.…”
Section: Introductionmentioning
confidence: 99%